2005
DOI: 10.1021/jf0480804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan on the Biological Properties of Sweet Basil (Ocimum basilicumL.)

Abstract: The effect of the treatment of chitosan at various concentrations (0.01%, 0.05%, 0.1%, 0.5%, and 1%) upon sweet basil (Ocimum basilicum L.) before seeding and transplanting was investigated in aspects of the amount of phenolic and terpenic compounds, antioxidant activity, and growth of the basil, as well as the phenylalanine ammonia lyase (PAL) activity. The total amount of the phenolic and terpenic compounds increased after the chitosan treatment. Especially, the amounts of rosmarinic acid (RA) and eugenol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
93
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(121 citation statements)
references
References 38 publications
13
93
1
3
Order By: Relevance
“…2.3 fold). Similar results were reported with cultures of Solanum tuberosum L. and Ocimum basilicum L. [45,46]. 6.6.3.5.…”
Section: Effect Of Different Elicitors and Salts On Callus Biomass Gasupporting
confidence: 88%
“…2.3 fold). Similar results were reported with cultures of Solanum tuberosum L. and Ocimum basilicum L. [45,46]. 6.6.3.5.…”
Section: Effect Of Different Elicitors and Salts On Callus Biomass Gasupporting
confidence: 88%
“…Cai et al [2011] have been reported that treatment with chitosan efficiently enhanced biosynthesis of phenolic compounds in Vitis vinifera. Similarly, Kim et al [2003] reported that total amount of the phenolic and terpenic compounds in sweet basil increased after the chitosan treatment.…”
Section: Resultsmentioning
confidence: 84%
“…Significant improvements in growth have been reported in daikon radishes (Raphanus sativus) [159], cabbage (Brassica oleracea) [22], soybean sprouts [160], sweet basil [161], grapevine [162], as well as ornamental crops, such as Gerbera [163] and Dendrobium orchids [164].…”
Section: Plant Growth Promotionmentioning
confidence: 99%